Evolving landscape of scholarly journals in open access environment. Issue 6 (2nd September 2019) - Gul, Sumeer; Gupta, Sangita; Shah, Tariq Ahmad; Nisa, Nahida Tun; Manzoor, Shazia; Rasool, Rehana
Abstract : Purpose: Open access journals (OAJs) offer immediate, free and unrestricted online access to the scholarly literature. The purpose of this study is to trace the status and characteristics of OAJs published across the globe. Various trends that have evolved in OAJ market have been studied. Design/methodology/approach: The study is based on data collected from one of the largest OA journal directory – Directory of Open Access Journals (DOAJ). The data were downloaded on 02 January 2018 and details of OAJs added to DOAJ till 31 December 2018 were harvested, codified and further analyzed in SPSS software. A Microsoft-Excel template application – MAKESENS – developed by Finnish Meteorological Institute (Finland) in 2002, was explored to perform Mann–Kendall Test and Sen's Slope Estimates. Findings: A less score of OAJs offer access to their archival content. An increasing trend is witnessed in the OAJ publishing with Elsevier, Sciendo and BioMed Central (BMC) as the top publishers. Majority of publishers are from high-income zone countries, followed by upper-middle and lower-middle zone countries. Majority of OA publishers are from the UK, Indonesia and Brazil. A lesser score of journals offer article processing charges and/or author submission charges. Majority of OAJs from high- and lower-middle-income zone countries levy submission/processing charge to authors compared to OA journals from upper-middle- and lower-income zone countries ( p < 0.01). OJS stays a prioritized platform for hosting OA journal content. Portico and CLOCKSS/LOCKSS are mostly used for long-term preservation purposes. Majority of OAJs from high-income zone countries participate in digital arching initiatives compared to ones from other income zones. Majority of the journals adopt a peer review (double-blind peer review, blind peer review, peer review and open peer review) process for validation of their scholarly content. The time lag between submission and publication ranges from one to 53 weeks, with majority of OAJs having a time lag of 11-20 weeks. Creative Commons Licenses are mainly adopted by OAJs. Research limitations/implications: As the study is based on the data offered by DOAJ, any gaps in the DOAJ data will also get reflected in the study. Further, there might be other OAJs also that have yet to show compliance with DOAJ standards and get indexed with it. Originality/value: The study tries to showcase the current status and characteristics of OAJs.